Maxıllary Orthopedıc And Orthodontıc Approach In Cleft Lıp And Palate - Ayhan Enacar; Mehmet Özgen; Murat Demirhanoğlu; Hasan Ayral; Tuğrul Altay (Galenos Yayinevi, 1993)
In the reestablishment of the impaired function and facial esthetics of the cleft lip and palate patients, orthodontic and maxillary orthopedic treatment has a determinant contribution within a multidisciplinary team approach. This philosophy of therapy is rendered in two time periods, a) Preoperative maxillary orthopedic treatment or infant orthopedics, b) Postoperative maxillary orthopedic and orthodontic treatment. Currently the benefits of early rnaxillary orthopedic treatment are still controversial The objective pursued here is to help establish a maxillary arch form as a fundamental base prior to the closure of the lip without the formation of the scar tissue. There is substantial evidence that the main factor restraining the development of the maxilla is not the early palatoplasty but failure of the lip construction. In the postoperative period, treatment is concentrated on the expansion of the collapsed rnaxillary arch and/or anterior maxillary growth stimulation via orthopedic force application. The intention of this paper is to present the pre and post operative treatment rationale of our clinic in CLP patients.